View of the basal mouldings of the Jain Temple - Temples of India Project Team (Jio Institute, 2024)
Closer view of the basal mouldings of the Jain Temple which show a plain moulding at the bottom followed by a curved moulding, a slender kani moulding, a band of kirtimukhas (face of glory) known as graaspatti, kumbha (pot-shaped) moulding, kalasha (a pitcher) moulding and finally two kapotali (cyma recta) mouldings. All these mouldings are beautifully crafted but do not have much surface ornamentation. The kumbha has a band of diamonds running all across the temple.